2014
DOI: 10.3892/etm.2014.2015
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium chloride suppresses acute rejection and induces tolerance following rat liver transplantation by inhibiting Kupffer-cell activation

Abstract: The aim of the present study was to investigate the mechanism by which gadolinium chloride (GdCl3) inhibits Kupffer cell (KC) activation and its ability to suppress acute rejection and induce tolerance following liver transplantation in rats. Rats were randomly divided into control, liver transplantation with GdCl3 pretreatment and liver transplantation with normal saline pretreatment groups. The survival rate, liver function, hepatic pathological histology, cytokine levels in the liver and bile, activity of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…An intriguing direct strategy involves use of gadolinium chloride to inhibit KC activation. This drug has shown promise in animal models of liver transplantation where administration of gadolinium chloride reduced markers of liver injury and improved hepatic blood flow . Unfortunately at this time, no correlative human data exist.…”
Section: Therapeutics For Hepatic Irimentioning
confidence: 99%
“…An intriguing direct strategy involves use of gadolinium chloride to inhibit KC activation. This drug has shown promise in animal models of liver transplantation where administration of gadolinium chloride reduced markers of liver injury and improved hepatic blood flow . Unfortunately at this time, no correlative human data exist.…”
Section: Therapeutics For Hepatic Irimentioning
confidence: 99%
“…115 However, other studies have found a beneficial outcome on liver allograft survival after gadolinium chloride treatment in other animal models. 116, 117 In mice, deletion of KCs with clodronate liposomes in donor liver allografts does not affect their acceptance. 118 …”
Section: Tolerance During Liver Transplantationmentioning
confidence: 99%
“…115 However, other studies have found a beneficial outcome on liver allograft survival after gadolinium chloride treatment in other animal models. 116,117 In mice, deletion of KCs with clodronate liposomes in donor liver allografts does not affect their acceptance. 118 Immunoregulatory mechanisms to maintain long-term tolerance in the liver Mechanisms that establish tolerance immediately after transplantation are sufficient to prevent early graft rejection, but may not Role of Tregs and other regulatory mechanisms.…”
Section: Early Mechanisms Of Tolerance Induction Within the Liver Graftmentioning
confidence: 99%
“…The dose of gadolinium chloride used in this study showed no toxicological effects when injected intravenously into rats 10,11 . Both agents were purchased from R & D Systems, Inc. Minneapolis, MN, USA as preservative-free reagents.…”
Section: Treatment Of Rats With Agentsmentioning
confidence: 99%